Benchmark pre-production practice in manufacturing engineering - Shehab, Essam; Rao, Yogeesh; Al-Ashaab, Ahmed; Beadle, Chris; Sarfraz, Shoaib (IOS Press, 2017)
Prototyping stage is a very important phase of new product development, where many decisions need to be taken to get high quality, zero defect products at the right time with minimum cost. Therefore, any value added improvements or best practices in the prototyping stage will support competitiveness of manufacturing companies. This research aims to benchmark the best practices in prototype part manufacture to support early stages of product introduction. A set of of best practices in the prototype component manufacture, along with validated four step prototyping strategy model and best practice prototype journey path model were developed. Research findings provide insight about prototyping trends, best practices and optimum ways of doing prototyping in the manufacturing companies around the globe. Manufacturing companies can use the developed models and best practices to make better prototype strategy in their new product introduction system to achieve their business objectives.
Keywords: New product introduction; prototype; pre-production; benchmark